Ethical and normative implications of weather event attribution for policy discussions concerning loss and damage - Thompson, A; Otto, FEL (Springer Netherlands, 2015)
Extreme weather events, at least in the short term, will arguably cause more damage and thus adversely affect society more than long term changes in the mean climate that are attributed to anthropogenic greenhouse gas emissions. While it was long perceived as impossible to directly link a singular event with external climate drivers the emerging science of probabilistic event attribution renders it possible to attribute the fraction of risk caused by anthropogenic climate change to particular weather events and their associated losses. The robust link of only a small fraction of excessive deaths in, e.g., a heatwave to manmade climate change is very significant from an ethical point of view and we argue that this has widespread implications, e.g. for pending policy decisions concerning the Warsaw International Mechanism for Loss and Damage and the recognition of such losses in the broader context of climate justice.